1989
DOI: 10.1161/01.cir.80.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Failure of atrial natriuretic factor to increase with volume expansion in acute and chronic congestive heart failure in the dog.

Abstract: It remains unclear whether the levels of atrial natriuretic factor (ANF) observed in chronic CHF are appropriate for the magnitude of elevations in atrial pressures. Specifically, it is not known whether acute increases in atrial pressure in CHF can result in further significant increases in circulating ANF. The present study was designed to test the hypothesis that in chronic CHF there is an attenuated relation between circulating ANF and atrial pressure such that the heart is unable to respond to further inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 23 publications
0
19
1
1
Order By: Relevance
“…A blunted natriuretic response after pharmacological doses of ANP and BNP has been observed in experimental models and in patients with chronic HF, suggesting a resistance to the biological effects of CNHs, principally natriuresis (10,73,100). As discussed in detail previously (11,16), resistance to the biological action of CNHs can be attributed at least to three different causes/mechanisms, acting at prereceptor, receptor, and postreceptor levels, respectively ( Table 3).…”
Section: Resistance To the Biological Effects Of Cnhsmentioning
confidence: 66%
“…A blunted natriuretic response after pharmacological doses of ANP and BNP has been observed in experimental models and in patients with chronic HF, suggesting a resistance to the biological effects of CNHs, principally natriuresis (10,73,100). As discussed in detail previously (11,16), resistance to the biological action of CNHs can be attributed at least to three different causes/mechanisms, acting at prereceptor, receptor, and postreceptor levels, respectively ( Table 3).…”
Section: Resistance To the Biological Effects Of Cnhsmentioning
confidence: 66%
“…Dogs were then paced for 8 days, which resulted in the clinical signs of CHF. 17,18 The dogs were fasted overnight before the acute experiment and given an oral dose of lithium (300 mg). Before the acute experiment, the dogs were anesthetized with fentanyl (0.005-0.01 mg/kg) and sodium pentobarbital (5-10 mg/kg) given intravenously.…”
Section: Methodsmentioning
confidence: 99%
“…In chronic severe CHF, however, the synthetic capacity of the atria may be overwhelmed relative to the demands of the system, leading to a state of relative deficiency. Indeed, Redfield et al [20] demonstrated in chronic severe experimental CHF an impaired capacity to release ANP in response to acute volume expansion with increases in atrial pressures. Volpe et al [21] have also demonstrated an impaired release of ANP in humans with dilated cardiomyopathy and severe CHF during acute volume expansion.…”
Section: Introductionmentioning
confidence: 99%